Natural Products and Cancer Drug Discovery - Badria, Farid A. (IntechOpen, 2017)
This book, Natural Products and Cancer Drug Discovery, is written by leading experts in natural products in cancer therapy. The first two sections describe new applications of common herbs and foods for treatment of cancer. Section 3 deals with the development of new chemotherapeutics from Cannabis and endophytic fungi. Section 4 presented formulations of natural products for treatment of malignant melanoma. Made-to-order anticancer therapy from natural products using computational and tissue engineering approaches is addressed in the fifth section. It is our hope that this book may motivate readers to approach the evidence of anticancer natural products with an open mind and thereby spark an interest in making further contributions to the cancer treatment efforts.